On the Problems of Early Diagnosis of Interstitial Lung Diseases in Children (Analysis of Clinical Cases) - S.I. Ilchenko; V.I. Cherhinets; A.O. Fialkovska; S.H. Ivanus; O.R. Prykhodko (Zaslavsky O.Yu., 2016)
The article presents the published data on the prevalence, etiology, pathogenesis, the main clinical manifestations, modern methods of early diagnosis and prognosis of interstitial lung diseases in children. The case of our own clinical observation of interstitial lung disease in a child aged 5 months is presented. Peculiarities of the course and manifestation of clinical signs of the disease in this patient are shown. This case demonstrates the complexity of early diagnosis of interstitial lung diseases in children, and timely diagnosis at an early, still reversible stages of the disease and adequate treatment can prevent progression of the disease and improve the prognosis.